The Social Context of Early Child Second Language Acquisition (SLA) - Maslihatul Umami (Register Journal, 2011)
This article addresses the material on language acquisition in a social context and focuses on the gradual shift in the child’s use of words, from labeling specific and often single referents to the use of words for signifying categories of objects, actions, or attributes. The aims of this study are to search and explore the information whether the social context of second language acquisition occurred and whether it gives consequences toward cognitive development of the children. It can be seen from the results of this study that the rate and breadth of this shift varies from one social context to another, and that it has differential consequences for cognitive development dependent on the social context in which it occurs. The crucial significance of actively stimulating language growth in the classroom, especially by teachers of the socially disadvantaged, is stressed.keywords; Social Context; Second Language Acquisition ; Children